2023
DOI: 10.3390/nu15112549
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Selenium Level and Self-Reported History of Kidney Stone

Abstract: A relationship may exist between selenium and kidney calculi, but there is a lack of research in this field at present. Our study explored the relationship between the serum selenium level and a medical history of adult kidney calculi. We utilized data from the National Health and Nutrition Examination Survey conducted between 2011 and 2016. Participants self-reported their history of kidney stones, while serum selenium levels were measured using inductively coupled plasma dynamic reaction cell mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Selenium, an essential trace element for the human body, enhances antioxidative capacity, scavenges free radicals, reduces oxidative damage caused by reactive oxygen species to the kidneys, and inhibits oxalate synthesis ( 42 ). A cross-sectional study utilizing NHANES data discovered a negative correlation between serum selenium levels and the risk of kidney stones ( 43 ). Another study demonstrated an inverse relationship between dietary selenium intake and kidney stone risk, particularly among young men (<50 years) and overweight or obese individuals (BMI ≥ 25.0) ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selenium, an essential trace element for the human body, enhances antioxidative capacity, scavenges free radicals, reduces oxidative damage caused by reactive oxygen species to the kidneys, and inhibits oxalate synthesis ( 42 ). A cross-sectional study utilizing NHANES data discovered a negative correlation between serum selenium levels and the risk of kidney stones ( 43 ). Another study demonstrated an inverse relationship between dietary selenium intake and kidney stone risk, particularly among young men (<50 years) and overweight or obese individuals (BMI ≥ 25.0) ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an inverse association between serum selenium levels and the risk of kidney stone history in the general population. Nevertheless, after conducting age-stratified analysis, only higher serum selenium levels remained significantly negatively associated with kidney stone risk in individuals aged 40–59 years; no significant benefit was observed for those over 60 years old ( 43 ). This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the impact of OBS on kidney stone risk may vary across different population subgroups, possibly due to differences in genetic susceptibility, dietary habits, or other lifestyle factors. A review (Wang et al, 2023) examined health disparities in kidney stone disease concerning race, ethnicity, socioeconomic status, and place of residence, and found that white males had the highest risk of Frontiers in Physiology frontiersin.org kidney stones. A study based on the NHANES database (Feng et al, 2021) found that males, non-Hispanic white people, and obese individuals had a higher prevalence of kidney stones, and the prevalence in females showed a catching-up trend.…”
Section: Discussionmentioning
confidence: 99%